2020
DOI: 10.3892/etm.2020.9396
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial dysfunction and pancreatic islet β‑cell failure (Review)

Abstract: Pancreatic β-cells are the only source of insulin in humans. Mitochondria uses pyruvate to produce ATP as an intermediate link between glucose intake and insulin secretion in β-cells, in a process known as glucose-stimulated insulin secretion (GSIS). Previous studies have demonstrated that GSIS is negatively regulated by various factors in the mitochondria, including tRNA Leu mutations, high p58 expression, reduced nicotinamide nucleotide transhydrogenase activity, abnormal levels of uncoupling proteins and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 146 publications
(263 reference statements)
0
19
0
Order By: Relevance
“…Under the stimulation of oxidative stress, the mitochondrial membrane potential (ΔΨm) will be changed, which is characterized by the disordered membrane potential leads to the opening of mitochondrial pores, thus releases cytochrome C into the cytoplasm, which in turn triggers the downstream apoptotic cascade [22,23]. AI-Nahdi et al RIN-m5F cells are a widely used insulin-secreting cell line, mainly containing insulin and a small amount of glucagon and somatostatin [17].…”
Section: Discussionmentioning
confidence: 99%
“…Under the stimulation of oxidative stress, the mitochondrial membrane potential (ΔΨm) will be changed, which is characterized by the disordered membrane potential leads to the opening of mitochondrial pores, thus releases cytochrome C into the cytoplasm, which in turn triggers the downstream apoptotic cascade [22,23]. AI-Nahdi et al RIN-m5F cells are a widely used insulin-secreting cell line, mainly containing insulin and a small amount of glucagon and somatostatin [17].…”
Section: Discussionmentioning
confidence: 99%
“…T2D is preceded by years of prediabetes, during which the elevation of blood glucose exerts deleterious effects on β-cell mitochondria and impairs insulin secretion [2,4,5,8,11,12,[25][26][27]. On the other hand, disrupting the mitochondrial oxidative metabolism blocks GSIS [1][2][3].…”
Section: Discussionmentioning
confidence: 99%
“…An abnormal mitochondrial morphology and reduced GSIS have been found in β cells from postmortem T2D patients [8][9][10]. Impairments in OxPhos [16,28,29] and diminished mitochondrial activity have been demonstrated in diabetes patients [2,4,11,12,27,[30][31][32][33][34][35], while mutations in the mitochondrial genome such as the mtDNA 3243 mutation were shown to be associated with diabetes [36][37][38][39][40]. More specifically, OxPhos genes were differentially expressed, and DNA methylation was found in these genes in islets from patients with T2D compared with nondiabetic donors [13,14].…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress plays a key role in the pathophysiology of insulin resistance and diabetes, via various molecular mechanisms, including beta cell dysfunction, inflammatory responses and mitochondrial dysfunction [54,55]. Researchers have also shown that oxidative stress is involved in the pathophysiology of diabetic cardiomyopathy and heart failure [7].…”
Section: Discussionmentioning
confidence: 99%